O trem, a fábrica e as caatingas: Perspectivas de modernização do sertão baiano na Primeira República - Guimarães, Eudes Marciel Barros [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2017)
With the installation of a factory and the possibility to introduce a railroad in the early 1910s, there were great expectations by some engaged men in the modernization of the region called alto sertão da Bahia [high hinterland in Bahia], according to the growth rate that was projected for Brazil. For this, they emphasized the economic power of backlands and the need to explore them, bearing in mind the variety and natural resources of the caatingas. However promising experiences that they had were substituted, often, to sorrow frustration along the after years.
The train, the factory and the caatingas: Perspectives of modernization of Bahia's backland in First Brazilian Republic
Keywords: Modernization; Social imaginary; Upper backland of Bahia